Development and Evaluation of a Hybrid Course in Clinical Virology at a Faculty of Pharmacy in Lille, France - Goffard, Anne (JMIR Med Educ, 2019)
BACKGROUND: During their studies, pharmacy students must acquire the specific skills in clinical virology required for their subsequent professional practice. Recent experiments on teaching and learning in higher education have shown that hybrid courses strengthen the students’ commitment to learning and enable high-quality knowledge acquisition. OBJECTIVE: This study concerned the design and deployment of a hybrid course that combines face-to-face and Web-based instruction in clinical virology for fourth-year pharmacy students. The study’s objectives were to (1) measure the students’ level of involvement in the course, (2) gauge their interest in this type of learning, and (3) highlight any associated difficulties. METHODS: The study included 194 fourth-year pharmacy students from the Lille Faculty of Pharmacy (University of Lille, Lille, France) between January and June 2017. The students followed a hybrid course comprising an online learning module and 5 tutorial sessions in which professional situations were simulated. The learning module and 3 online evaluation sessions were delivered via the Moodle learning management system. Each tutorial session ended with an evaluation. The number of Moodle log-ins, the number of views of learning resources, and the evaluation marks were recorded. The coefficient for the correlation between the marks in the online evaluation and those in the tutorials was calculated. The students’ opinions and level of satisfaction were evaluated via a course questionnaire. RESULTS: The course’s learning resources and Web pages were viewed 21,446 and 3413 times, respectively. Of the 194 students, 188 (96.9%) passed the course (ie, marks of at least 10 out of 20). There was a satisfactory correlation between the marks obtained in the online evaluations and those obtained after the tutorials. The course met the students’ expectations in 53.2% of cases, and 57.4% of the students stated that they were able to work at their own pace. Finally, 26.6% of the students stated that they had difficulty organizing their work around this hybrid course. CONCLUSIONS: Our results showed that pharmacy students were strongly in favor of a hybrid course. The levels of attendance and participation were high. However, teachers must be aware that some students will encounter organizational difficulties.